Continuing professional development towards teachers' performance at vocational secondary schools in Surakarta - Isti Setya Rini; Ismi Dwi Astuti Nurhaeni; C. Dyah Sulistyaningrum Indrawati (Jurnal Pendidikan Vokasi, 2019)
Continuing Professional Development is a program from the government so that teachers can develop their performance. Continuing Professional Development includes: self-development, scientific publications, and innovative work. This study aims to determine the effect of Sustainable Professional Development (self-development, scientific publications, and innovative work) on the performance of vocational business and management teachers in Surakarta. This study uses a quantitative method with Structural Equation Modeling Partial Least Square (SEM-PLS) analysis. The study sample was 158 business and management vocational teachers in Surakarta, Indonesia. The results of the study show that 1) self-development has a positive and significant influence on teacher performance of 0.333 and the statistical value of T is 5.028â‰¥1.96; 2) scientific publications have a positive and significant effect on teacher performance of 0.225 and T statistical values of 1.763â‰¤1.96; and 3) innovative works have a positive and significant effect on teacher performance of 0.282 and the value of T statistics is 1.810 .91.96. Therefore, vocational business and management teachers need to improve professional development through scientific publications and innovative work.